First Occurrence Of The Tilapia Oreochromis Niloticus Niloticus (Linnaeus, 1758) In Lesina Lagoon (Eastern Italian Coast) - SCORDELLA, G.; LUMARE, F.; CONIDES, A.; PAPACONSTANTINOU, C. (Mediterranean Marine Science, 2003)
Individuals of the tilapia species Oreochromis niloticus niloticus(Linnaeus, 1758) were caught in Lesina Lagoon during experimental sampling for the shrimp Penaeus kerathurus using fyke net traps from December 1999 to September 2000. The species O. niloticusis not native in Italian coastal waters, although attempts of tilapia culture in land-based aquaculture farms were occasionally carried out in the past. The number of individuals captured in the samples suggests a colonization of the area of Lesina lagoon. The highest catches were observed during July. In July, the individuals caught represented the 22.3±4.1 % of the total catch weight. Such colonization of a marine environment byO. niloticusniloticus is the first case reported for Italy. The occurrence of the species in Lesina lagoon is attributed to fish which escaped from fish farms in the area and entered the lagoon through the numerous streams and irrigation-drainage channels that outflow along the south coastline.